Effects of Neonatal Thoracoscopic Surgery on Tissue Oxygenation: A Pilot Study on (Neuro-) Monitoring and Outcomes - Costerus, Sophie; Vlot, John; van Rosmalen, Joost; Wijnen, René; Weber, Frank (European Journal of Pediatric Surgery, 2019)
Introduction Multiple reports have questioned the feasibility of neonatal thoracoscopic repair of congenital diaphragmatic hernia (CDH) and esophageal atresia (EA). The aim of this study is to examine the effects of CO2 pneumothorax on cerebral and renal rSO2 and to assess the potential predictive value of these data on neurodevelopmental outcome after neonatal thoracoscopic surgery for CDH or EA.Materials and Methods A prospective observational pilot study. Cerebral and renal regional tissue oxyhemoglobine saturation (rSO2) rSO2 were assessed using near-infrared spectroscopy (NIRS) during thoracoscopic surgery in neonates with CDH and with EA, in addition to routine anesthesia monitoring. Cerebral and renal rSO2, linked to repeated arterial blood gas analyses, heart rate, blood pressure, and to structured longitudinal neurodevelopmental follow-up.Results Baseline estimated marginal means of cerebral rSO2 values (CDH: 82%, EA: 91%) did not change significantly during pneumothorax (CDH: 81%, EA 79% [n.s. versus baseline]) despite severe acidosis (lowest pH, CDH: 6.99, EA: 7.1). Neurodevelopmental outcomes at 24 months were normal in all 7 patients who were available for evaluation.Conclusion Neonatal thoracoscopic repair of CDH and EA using CO2-pneumothorax leads to severe acidosis. Cerebral rSO2 remained within clinical acceptable limits during intraoperative periods of acidosis. Neurodevelopmental outcome was favorable within the first 24 months. The potential of NIRS to further improve perioperative care and long-term outcome in this specific patient group deserves further investigation.
Keywords: congenital diaphragmatic hernia; atresia; esophageal; surgery; thoracoscopic; spectroscopy; near infrared; acidosis